Bloch‐Siegert B1+‐mapping for human cardiac 31P‐MRS at 7 Tesla. Issue 4 (28th October 2015) - Clarke, William T.; Robson, Matthew D.; Rodgers, Christopher T.
Abstract : Purpose: Phosphorus MR spectroscopy ( 31 P‐MRS) is a powerful tool for investigating tissue energetics in vivo. Cardiac 31 P‐MRS is typically performed using surface coils that create an inhomogeneous excitation field across the myocardium. Accurate measurements of B 1 + (and hence flip angle) are necessary for quantitative analysis of 31 P‐MR spectra. We demonstrate a Bloch‐Siegert B 1 + ‐mapping method for this purpose. Theory and Methods: We compare acquisition strategies for Bloch‐Siegert B 1 + ‐mapping when there are several spectral peaks. We optimize a Bloch‐Siegert sensitizing (Fermi) pulse for cardiac 31 P‐MRS at 7 Tesla (T) and apply it in a three‐dimensional (3D) chemical shift imaging sequence. We validate this in phantoms and skeletal muscle (against a dual‐TR method) and present the first cardiac 31 P B 1 + ‐maps at 7T. Results: The Bloch‐Siegert method correlates strongly (Pearson's r = 0.90 and 0.84) and has bias <25 Hz compared with a multi‐TR method in phantoms and dual‐TR method in muscle. Cardiac 3D B 1 + ‐maps were measured in five normal volunteers. B 1 + maps based on phosphocreatine and alpha‐adenosine‐triphosphate correlated strongly (r = 0.62), confirming that the method is T1 insensitive. Conclusion: The 3D 31 P Bloch‐Siegert B 1 + ‐mapping is consistent with reference methods in phantoms and skeletal muscle. It is the first method appropriate for 31 P B 1 + ‐mapping in the human heart at 7T. Magn Reson Med 76:1047–1058, 2016. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.